Manajemen Kesiswaan dan Pembentukan Karakter Disiplin Santri - Azizah, Putri Nur; Moh Sulhan; Heny Mulyani (IAIN Parepare, 2025)
This study aims to analyze the implementation of student management and its contribution to shaping the disciplinary character of students at Al-Basyariah Islamic Boarding School, which operates a 24-hour education system. The study addresses the empirical gap regarding the quantitative relationship between student management and student discipline, including the influence of external factors such as family and peers. A quantitative survey was conducted with 85 students. Data were analyzed using validity and reliability tests, normality and linearity checks, simple linear regression, and the coefficient of determination. Findings show that student management is well-implemented with a mean score of 4.16 (high category), while students’ disciplinary character scored 4.33 (very high category). The coefficient of determination of 0.335 indicates that student management contributes 33.5% to disciplinary character, while 66.5% is influenced by other factors. These results emphasize that structured and consistent student management is significant, yet effective discipline formation requires coordinated engagement between the school, family, and social environment.